2002
DOI: 10.2188/jea.12.199
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behavior and Related Lifestyle Variables among Physicians in Fukuoka, Japan: A Cross Sectional Study.

Abstract: A cross-sectional survey of the entire membership of the Fukuoka Prefecture Medical Association was conducted in 1983 using a self-administered questionnaire. In this investigation the actual prevalence of smoking among physicians and the relationship between their smoking habits and living habits were studied. The study subjects were divided into two groups: those who smoked (1,737 men and 17 women), and those who did not currently smoke (2,267 men and 169 women). It was realized that there were many who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
13
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
4
13
0
3
Order By: Relevance
“…The strong association between current smoking and irregular breakfasting was reported in previous studies [4,25]. In addition, a study that investigated associations between smoking and intake of various foodstuffs demonstrated lower consumption of fresh vegetables, yellow and green vegetables, and fruit by smokers [26]. These findings might suggest that smoking induced changes in taste or loss of appetite.…”
Section: Discussionsupporting
confidence: 52%
“…The strong association between current smoking and irregular breakfasting was reported in previous studies [4,25]. In addition, a study that investigated associations between smoking and intake of various foodstuffs demonstrated lower consumption of fresh vegetables, yellow and green vegetables, and fruit by smokers [26]. These findings might suggest that smoking induced changes in taste or loss of appetite.…”
Section: Discussionsupporting
confidence: 52%
“…Multiple investigations from Italy [40,48,53], Japan [41,51,62,78,83-85,100] and France [49,63] for example, have consistently documented smoking prevalence rates over 25%. A second trend is also evident in some newly developing countries, where contemporary physicians appear to be smoking at high rates in China [55], Estonia [31,32], Bosnia/Herzegovina [33] and Turkey [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that when a physician gives advice to quit smoking, the proportion of smokers who manage to give up smoking is increased (Kaetsu et al 2002;McIlvain et al 2002;Lancaster et al 2000). The recent evidence indicates that even brief fi rm advice to stop smoking can lead to an increase in long-term cessation rates of about 1-2% (Liu & Tang 1998;McEwen & West 2001).…”
mentioning
confidence: 99%
“…The recent evidence indicates that even brief fi rm advice to stop smoking can lead to an increase in long-term cessation rates of about 1-2% (Liu & Tang 1998;McEwen & West 2001). However, it is also reported that whether or not a physician advises a patient to stop smoking depends on the smoking status of that particular physician (Kaetsu et al 2002;Tessier et al 1993b). There is a risk that the advice of smoking physicians is affected by their individual assessment of the health consequences of smoking, which might not be in accordance with the evidence.…”
mentioning
confidence: 99%
See 1 more Smart Citation